2000
DOI: 10.1086/315283
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus in Lymphoid Cells of Patients Coinfected with Human Immunodeficiency Virus Type 1: Evidence of Active Replication in Monocytes/Macrophages and Lymphocytes

Abstract: It has been reported that hepatitis C virus (HCV) may be lymphotropic in the setting of human immunodeficiency virus type 1 (HIV-1) coinfection. The present study was undertaken to determine the phenotype of lymphoid cells harboring replicating HCV in HIV-1-positive subjects. By means of highly strand-specific thermostable enzyme Tth-based reverse-transcriptase polymerase chain reaction, the presence of viral RNA-negative strand was sought in different subpopulations of peripheral blood mononuclear cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(181 citation statements)
references
References 45 publications
13
165
0
Order By: Relevance
“…9 Because brain microglial cells are tissue-resident macrophages of blood monocytic origin, 13 we postulate that they also could support HCV replication. Our findings support this hypothesis because HCV replicative forms were detected in the CNS of both studied subjects, although the lineage of infected cells was not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Because brain microglial cells are tissue-resident macrophages of blood monocytic origin, 13 we postulate that they also could support HCV replication. Our findings support this hypothesis because HCV replicative forms were detected in the CNS of both studied subjects, although the lineage of infected cells was not established.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 For the purpose of sequence comparison, nested protocols were used to maximize the yield of PCR product. Amplification of 5Ј UTR was conducted using RT-PCR assay, as previously described.…”
Section: Analysis Of Hcv Quasispeciesmentioning
confidence: 99%
“…Supporting this, HCV replication in lymphoid cells has been shown in HIV-1 positive patients. 32 More recently, Sulkowski et al 33 showed no difference in the risk of death or in the risk of developing a new AIDS-defining illness in patients with and without HCV. Survival was reduced in HCV-infected patients with baseline CD4 cell counts from 50 cells/mm 3 through 200 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, negative-strand HCV RNA has been identified in a variety of non-hepatic tissues (Table 2), including the pancreas, thyroid, bone marrow, adrenal gland, spleen, lymph node, cervicovaginal fluid, and brain. 29,[67][68][69][70][71][72] Initial studies similarly reported extrahepatic replication of HCV in PBMCs (Table 3). 58,[73][74][75][76][77] However, as the detection assays were not able to adequately differentiate between positive-and negative-strand HCV RNAs, theses results should be interpreted with extreme caution.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%